Errata do twórczości Stanisława Czernika: rok 1949 - Gardocki, Wiktor (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The subject of this paper is the writing activity of Stanisław Czernik in 1949. Czernik was an esteemed writer but concurrently he worked as censor in The Ministry of Culture and Art. He reviewed novels of many writers in the same department of Ministry where his novels were reviewed as well. This paper discusses a number reviews wrote by Czernik and some reviews of Czernik’ books wrote by another censors of The Ministry.